ARGAMASSA DE ASSENTAMENTO MISTA E INDUSTRIALIZADA – COMPARAÇÃO ENTRE AS PROPRIEDADES FÍSICAS E MECÂNICAS PARA APLICAÇÃO EM ALVENARIA ESTRUTURAL - Filla, Gustavo; Salvador, Rafaella; Toralles, Berenice (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Due to the broad usage of industrial settlement mortar in structural brickwork, it becomes necessary to know about its physical and mechanical properties, just as well as the validation of its viability in constructions. In this way, this paper has the objective of analyzing properties of industrial mortar in comparison to the conventional mortar, as well as verify the coverage of industrial mortar in function of blocks compressive trenght. In order for this work to come to fruition, 3 different types of industrial mortar and 3 types of conventionalmortar were crafted. In turn, the final results showed that industrial mortar displayed great potential in structural brickwork application, due to the fact that they have satisfactory compression strength while showing great incorporated air rate, covering blocks with 20, 14 and 8 MPa. Besides that, in comparison with the conventional mortar, the industrial mortar has a racionalized fabrication process, presenting a greater quality control.